2007
DOI: 10.1002/art.23172
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase decreases type II collagen expression in bovine articular cartilage chondrocytes via the ERK signaling pathway

Abstract: Objective. Ceramide, a mediator of proinflammatory cytokine signaling, induces cartilage degradation and reduces type II collagen synthesis in articular cartilage. The accumulation of ceramide is associated with arthritis in Farber's disease. The aim of this study was to investigate the mechanism of ceramide-induced down-regulation of type II collagen.Methods. Bovine articular chondrocytes were stimulated with sphingomyelinase (SMase) to increase levels of endogenous ceramide. Components of the ERK pathway wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Ceramide might play a mediatory role in cartilage loss during OA due to increased chondrocyte apoptosis and by inducing proteoglycan degradation [89]. High levels of endogenous ceramide have been demonstrated to disrupt cartilage matrix homeostasis, resulting in down-regulation of type II collagen in articular cartilage [90,91]. In fact, acid ceramidase, by degrading ceramide, alters sphingolipid metabolism and improves chondrogenesis [92] (Figure 1).…”
Section: Lipids and Chondrocyte Metabolismmentioning
confidence: 99%
“…Ceramide might play a mediatory role in cartilage loss during OA due to increased chondrocyte apoptosis and by inducing proteoglycan degradation [89]. High levels of endogenous ceramide have been demonstrated to disrupt cartilage matrix homeostasis, resulting in down-regulation of type II collagen in articular cartilage [90,91]. In fact, acid ceramidase, by degrading ceramide, alters sphingolipid metabolism and improves chondrogenesis [92] (Figure 1).…”
Section: Lipids and Chondrocyte Metabolismmentioning
confidence: 99%
“…For example, an early report [13] showed that a synthetic ceramide derivative (C2 ceramide) stimulated the expression of matrix metalloprotease (MMP) −1, 3 and 13 in rabbit articular chondrocytes, and induced chondrocyte apoptosis. Gilbert et al [14] also showed that treatment of bovine articular chondrocytes with sphingomyelinase, an enzyme that produces ceramide by sphingomyelin hydrolysis, decreased expression of collagen II. Elevated ceramide also has been documented in patients with rheumatoid and osteoarthritis [15], and inhibition of sphingosine-1-phosphate (S1P) production in induced rodent models of arthritis has led to beneficial clinical results [16].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption in glycosphingolipid synthesis enhances the development of osteoarthritis in mice [42]. Studies have also examined roles for ceramides in the regulation of type II collagen synthesis via the ERK (extracellular-signal-regulated kinase) signaling pathway [43], proteoglycans and glycosaminoglycans [44][45][46] and MMPs by chondrocytes [47].…”
Section: Discussionmentioning
confidence: 99%